2019
DOI: 10.3390/cells8060596
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Profiling of Laron Syndrome Patients Identifies Novel Cancer Protection Pathways

Abstract: Laron syndrome (LS), or primary growth hormone resistance, is a prototypical congenital insulin-like growth factor 1 (IGF1) deficiency. The recent epidemiological finding that LS patients do not develop cancer is of major scientific and clinical relevance. Epidemiological data suggest that congenital IGF1 deficiency confers protection against the development of malignancies. This ‘experiment of nature’ reflects the critical role of IGF1 in tumor biology. The present review article provides an overview of recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 90 publications
(91 reference statements)
0
34
0
3
Order By: Relevance
“…Epidemiologic evidences indicated that high serum levels of IGF1 correlate with increased risk of cancer [ 21 , 22 ]. Accordingly, patients affected by Laron syndrome, a disease characterized by congenital deficiency of IGF1, do not develop cancer [ 23 ]. In 1993, Sell and colleagues demonstrated that the simian virus 40 large tumor antigen (SV40 TAg) was unable to transform fibroblasts derived from mouse embryos homozygous for a null mutation of the igf1r gene (R − cells) [ 20 ].…”
Section: The Igf System In Cancermentioning
confidence: 99%
“…Epidemiologic evidences indicated that high serum levels of IGF1 correlate with increased risk of cancer [ 21 , 22 ]. Accordingly, patients affected by Laron syndrome, a disease characterized by congenital deficiency of IGF1, do not develop cancer [ 23 ]. In 1993, Sell and colleagues demonstrated that the simian virus 40 large tumor antigen (SV40 TAg) was unable to transform fibroblasts derived from mouse embryos homozygous for a null mutation of the igf1r gene (R − cells) [ 20 ].…”
Section: The Igf System In Cancermentioning
confidence: 99%
“…This occurs especially in patients with molecular defects in the intracellular GH signaling pathway (STAT5B, STAT3, IKBKB, IL2RG, PIK3R1) [64]. Interestingly, patients with Laron syndrome do not develop cancer [66][67][68][69][70] and recent studies on genome-wide profiling of patients with this syndrome has been able to identify novel cancer protection pathways, opening the way to new developments in oncology [69,70]. These results, together with those of the studies in centenarians [70,71], seem to indicate a preventing effect of reduced secretion or lacking action of GH-IGF-1 on some diseases with increased life expectance.…”
Section: Genetic Alteration Affecting Gh and Igf-1 Actionsmentioning
confidence: 99%
“…PPP strongly inhibited FO-induced bone formation and growth rate, indicating that FO-mediated bone formation and growth performance require the presence of IGF-1. Recently, Werner et al reported that pituitary-produced GH leads to the secretion of IGF-1 by the liver into the systemic circulation, which causes bone elongation and longitudinal growth [ 33 ]. Mice lacking GH and IGF-1 receptor ( Gh − / − and IGF-1 − / − ) showed greater reduction in bone mass and length compared with the wild-type ( Ghr + / + and IGF-1 + / + ) mice, suggesting that GH and IGF-1 are important for bone formation [ 34 ].…”
Section: Discussionmentioning
confidence: 99%